INVESTMENT FUNDS ACTIVITIES AND THEIR STRATEGIES IN FOREIGN COUNTRIES (World Economics and Finance Bulletin, 2024)
The article provides information on the activities of investment funds in foreign countries and examines their distinctive features. Based on the research materials and methods, the experience and current status of investment funds by type in developed countries have been studied, and opinions have been expressed. During the research, index funds were explored in depth, and their effectiveness was analyzed. Conclusions were drawn based on the results of the research and analysis.
Keywords: International investment funds; stock; index funds